Andrews, Kevin. Audio interview about building wriggle fences - Crane, Katie (2020)
Kevin Andrews describes the process of building a wriggle fence. 00:00 Taught how to make wriggle fences by his uncles and grandfather; 00:35 Made his own wriggle fence with his wife; 00:52 Uses narrow sticks that bend easily, and cut them with the power saw; 01:15 Talks about the process of building the fence; 01:56 Before nails, wooden dowels were used to hold the fence together; 02:35 Took 8 hours to build an 8 foot fence; 02:47 Uses spruce or var wood; 03:01 Takes about 15 or 20 years before the fence needs to be rebuilt; 03:11 Can collect wood any time but make the fence in the summer because there is no frost; 03:32 Doesn't take many tools to construct; 04:08 Built the fence to teach his kids about the skill and to show them what it looked like because there were none of these fences left in his community; 04:54 Building the fence is a good learning experience; 05:09 Wriggle fences are good windbreaks; 05:26 Baccalieu Trail Traditional Skills Inventory project; 06:25 Taking photos of the fence